Adsorption of catechol and hydroquinone on titanium oxide and iron (III) oxide. Issue 5 (October 2020) - Abugazleh, Mohd Kotaiba; Rougeau, Benjamin; Ali, Hashim
Highlights: Maximum adsorption occurred at the pHpzc of each oxide, with pH influencing adsorption on TiO2, more than on Fe2 O3 . Pseudo second order-kinetics were found to explain the kinetic behavior on both oxides. Adsorption of hydroquinone on TiO2 /Fe2 O3 follows Freundlich model, while catechol on TiO2 follows Langmuir model. Abstract: The adsorption of catechol (CAT) and hydroquinone (HYD) on the surface of TiO2 (anatase) and Fe2 O3 (hematite) were investigated using attenuated total reflectance Fourier transform infrared spectroscopy. Linear and nonlinear regression together with error analysis methods were employed to identify the model that best explains the experimental data. Adsorption on these oxides was found to increase as pH was raised, reaching a maximum at the pHpzc of the respective oxide and decreasing as pH increased. Among the kinetic and adsorption models investigated, pseudo-second-order kinetic model and Freundlich adsorption model were found to fit the experimental data well, respectively. The maximum adsorption capacity for CAT was found to be 122.8 ± 33.1 mg g −1 and 361.2 ± 0.1 mg g −1, on TiO2 and Fe2 O3, respectively, averaged between pH, kinetic and adsorption studies. For HYD on Fe2 O3, the adsorption capacities were 86.12 mg g −1 and 58.49 mg g −1, while adsorption on TiO2 was 63.2 mg g −1 and 351.7 mg g −1, as calculated from pH and kinetic studies, respectively. It was also observed that TiO2 had higher HYD adsorption capacity than Fe2 O3, while CAT adsorption capacity was higher in Fe2 O3, than in TiO2, confirming that the nature of adsorbent can influence the adsorption of substrates on their surfaces.